Experimental evidence of Wolbachia introgressive acquisition between terrestrial isopod subspecies. Issue 4 (26th December 2020) - Bech, Nicolas; Beltran-Bech, Sophie; Chupeau, Cassandre; Peccoud, Jean; Thierry, Magali; Raimond, Roland; Caubet, Yves; Sicard, Mathieu; Grève, Pierre
Abstract: Wolbachia are the most widespread endosymbiotic bacteria in animals. In many arthropod host species, they manipulate reproduction via several mechanisms that favor their maternal transmission to offspring. Among them, cytoplasmic incompatibility (CI) promotes the spread of the symbiont by specifically decreasing the fertility of crosses involving infected males and uninfected females, via embryo mortality. These differences in reproductive efficiency may select for the avoidance of incompatible mating, a process called reinforcement, and thus contribute to population divergence. In the terrestrial isopod Porcellio dilatatus, the Wolbachia w Pet strain infecting the subspecies P. d. petiti induces unidirectional CI with uninfected individuals of the subspecies P. d. dilatatus . To study the consequences of CI on P. d. dilatatus and P. d. petiti hybridization, mitochondrial haplotypes and Wolbachia infection dynamics, we used population cages seeded with different proportions of the 2 subspecies in which we monitored these genetic parameters 5 and 7 years after the initial setup. Analysis of microsatellite markers allowed evaluating the degree of hybridization between individuals of the 2 subspecies. These markers revealed an increase in P. d. dilatatus nuclear genetic signature in all mixed cages, reflecting an asymmetry in hybridization. Hybridization led to the introgressive acquisition of Wolbachia and mitochondrial haplotype from P. d. petiti into nuclear genomes dominated by alleles of P. d. dilatatus . We discuss these results with regards to Wolbachia effects on their host (CI and putative fitness cost), and to a possible reinforcement that may have led to assortative mating, as possible factors contributing to the observed results.